Keragaman dan Kelimpahan Populasi Liriomyza spp. (Diptera : Agromyzidae) serta Parasitoidnya pada Pertanaman Sayuran Dataran Sedang dan Tinggi di Bali - PRATAMA, I PUTU ADNYA; SUSILA, I WAYAN; SUPARTHA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT The Diversity and Abundance of Liriomyza spp. (Diptera : Agromyzidae) and their Parasitoids on Middlelands and Highlands Vegetable Crops in Bali This research was conducted in the laboratory of Integrated Plant Pest and Disease Management, Department of Plant Protection, Faculty of Agriculture, Udayana University. The purpose of this research is to know the abundance, diversity and distribution populations of Liriomyza spp. and their parasitoids on middle- and highlands vegetable crops in Bali. Results of the research indicated that there are two  species of Liriomyza and five parasitoids associated with vegetable crops on middle- and highlands in Bali. Both species of Liriomyza are L. sativae and L. huidobrensis . The highest abundance populations of L. sativae was found on tomato plants, whereas L. huidobrensis found on potato plants. The research also indicated that there were five species of parasitoids associated with L. sativae and L. huidobrensis on middle- and highlands vegetable crops in Bali. Those parasitoids were Neochrysocharis formosa , Neochrysocharis okazakii , Hemiptarsenus varicornis , Asecodes deluchii (Eulophidae) and Opius sp. (Braconidae). Among those, N. okazakii, N. formosa and Opius sp. were the most dominant parasitoids associated with L. sativae and L. huidobrensis , showed by their highly populations abundance and parasitization level to the host. Key words : Diversity, Populations abundance, Liriomyza spp ., vegetable crops, Parasitoids.
Keywords: diversity; Populations abundance; Liriomyza spp.; vegetable crops; Parasitoids